2009
DOI: 10.1097/jto.0b013e3181914d3a
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Treatment of Poor-Risk Patients with Stage I Lung Cancer: A Single Institution Experience

Abstract: Medical inoperability does not necessarily correspond to poor survival in patients with early stage NSCLC. A nihilistic approach is not warranted towards this population, and prospective trials are needed to better define optimal treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The majority of studies considered RFA (n=25 studies)266290 and SABR (n=14)262 265 291–302. Other publications reported outcomes from conventional radiotherapy (n=3),281 297 303 percutaneous cryotherapy (n=1),276 microwave ablation (n=2)304 305 inhaled corticosteroids (n=2)306 307 and antibiotics (n=1) 308…”
Section: Non-surgical Treatment Without Pathological Confirmation Of mentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of studies considered RFA (n=25 studies)266290 and SABR (n=14)262 265 291–302. Other publications reported outcomes from conventional radiotherapy (n=3),281 297 303 percutaneous cryotherapy (n=1),276 microwave ablation (n=2)304 305 inhaled corticosteroids (n=2)306 307 and antibiotics (n=1) 308…”
Section: Non-surgical Treatment Without Pathological Confirmation Of mentioning
confidence: 99%
“…Hsie et al 281 retrospectively compared outcomes in 96 patients with pathologically confirmed stage I NSCLC not suitable for standard surgical resection (lobectomy/pneumonectomy) and treated with either limited surgical resection, RFA or conventional radical radiotherapy. Patients were assigned to treatment groups by clinician preference and the cohorts were not well matched.…”
Section: Non-surgical Treatment Without Pathological Confirmation Of mentioning
confidence: 99%
See 2 more Smart Citations
“…The rationale for conventional LR centers around improving early survival and quality of life, and preoperative risk analysis should be cautiously focused on precise assessment of risk-benefit relationship on an individual patient basis. Because patients with stage I NSCLC who are indicated for non-surgical treatment due to multiple risk factors are rare, there have been only a few reports on the long-term outcome of CRL in comparison to radiotherapy or chemotherapy [12,13] for this subset. In our study, the overall surgical outcome after CRL was less than optimal with high recurrence rate.…”
Section: Discussionmentioning
confidence: 99%